STRATEGI PROMOSI MADRASAH DI MEDIA SOSIAL DALAM MENARIK ANIMO PESERTA DIDIK BARU - M. Yusuf; Fatiha Ni’matul Maula (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
In the midst of the rapid demands to keep up with current technological developments, an educational institution is required to continue to innovate in increasing the existence of the institution by promoting through digital media. Promotions uploaded to social media will be able to attract the interest of new students more effectively than only using print media. There are several social media platforms that can be used to promote educational institutions. So then, how can promotion on social media be properly achieved to attract the interest of new students? Of course, it takes planned steps and strategies to achieve all of that. This type of research is descriptive with a qualitative approach. Data collection techniques using semi-structured interviews, non-participant observation, and documentation Data analysis techniques used are data reduction, presentation, and verification. Test the validity of the data using source triangulation techniques, peer discussions, and member checks. The results of the promotion strategy on social media in increasing the interest of new students are influencing the interest of new students, influencing decision-making in choosing schools, facilitating the delivery of information, and increasing the interest of new students.   Keywords: Strategy, Promotion, Social Media, And New Student Interest